El estudio arqueológico del ritual - Centeno Sara-Lafosse, Rafael Vega (2006)
This is a methodological frame for the study of ritual, understood as a significant social practice, from an archaeological perspective. In order to develop this goal, the social significance of ritual within human groups is discusses. In addition, some trans-cultural characteristics of ritual practices are signaled, as well as their material correlates. On the basis of this discussion, some methodological guidelines on the relation between those correlates and the archaeological record are evaluated. A special emphasis is given to the nature of discard processes of ritual artifacts and objects, as well as to the characteristics of the architectural design of ritual spaces. Two dimensions of architectural design are evaluated: the spatial structure and the perceptual structure.